Glycol Chitosan/Heparin Immobilized Iron Oxide Nanoparticles with a Tumor-Targeting Characteristic for Magnetic Resonance Imaging - Yuk, Soon Hong; Oh, Keun Sang; Cho, Sun Hang; Lee, Beom Suk; Kim, Sang Yoon; Kwak, Byung-Kook; Kim, Kwangmeyung; Kwon, Ick Chan (AMER CHEMICAL SOC, 2011)
We described the preparation of the glycol chitosan/heparin immobilized iron oxide nanoparticles (composite NPs) as a magnetic resonance imaging agent, with a tumor-targeting characteristic. The iron oxide nanoseeds used clinically as a magnetic resonance imaging agent were immobilized into the glycol chitosan/heparin network to form the composite NPs. To induce the ionic interaction between the iron oxide nanoseeds and glycol chitosan, gold was deposited on the surface of iron oxide nanoseeds. After the immobilization of gold-deposited iron oxide NPs into the glycol chitosan network, the NPs were stabilized with heparin based on the ionic interaction between cationic glycol chitosan and anionic heparin. FE-SEM (field emission-scanning electron microscopy) and a particle size analyzer were used to observe the formation of the stabilized composite NPs, and a Jobin-Yvon Ultima-C inductively coupled plasma-atomic emission spectrometer (ICP-AES) was used to measure the contents (96) of formed iron oxide nanoseeds as a function of reaction temperature and formed gold deposited on the iron oxide nanoparticles. We also evaluated the time-dependent excretion profile, in vivo biodistribution, circulation time, and tumor-targeting ability of the composite NPs using a noninvasive NIR fluorescence imaging technology. To observe the MRI contrast characteristic, the composite NPs were injected into the tail veins of tumor bearing mice to demonstrate their selective tumoral distribution. The MR images were collected with conventional T-2-weighted spin echo acquisition parameters.
Keywords: MACROPHAGE ENDOCYTOSIS; MECHANISMS; PACLITAXEL; TRANSPORT